2015
DOI: 10.15381/rivep.v26i2.11094
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparásitos en Palomas Columba livia Comercializadas en un Mercado del Distrito de San Martín de Porres, Lima, Perú

Abstract: El objetivo del presente trabajo fue determinar la prevalencia, intensidad media y abundancia media de ectoparásitos en palomas domésticas (Columba livia) comercializadas en un mercado de la ciudad de Lima, Perú. Se analizaron 29 ejemplares (17 machos y 12 hembras). Se inspeccionó la superficie externa de la cabeza, cuello, pecho, dorso y alas, determinando que el 93.1% (14.9 ± 15.8 de abundancia media total) de las palomas estuvieron infestadas con uno o más ectoparásitos; asimismo, el 100 de los machos y 83.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…This host bird has been studied in Brazil by Amaral et al (2017) who reported the same species of ectoparasites in their study. In Peru, different authors have reported the same association of ectoparasites with the host, found in C. columbae (Naupay et al, 2015;Castro et al, 2017), C. turbiratum and C. compar (Dale, 1970), however, it was not previously reported for H. lata. The diversity of ectoparasites in C. livia could be attributed to the fact that this species has a close interaction with domestic and wild birds, in addition to being located in different parts of the city, which can generate a cross contagion (Begum & Sehrin, 2011).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This host bird has been studied in Brazil by Amaral et al (2017) who reported the same species of ectoparasites in their study. In Peru, different authors have reported the same association of ectoparasites with the host, found in C. columbae (Naupay et al, 2015;Castro et al, 2017), C. turbiratum and C. compar (Dale, 1970), however, it was not previously reported for H. lata. The diversity of ectoparasites in C. livia could be attributed to the fact that this species has a close interaction with domestic and wild birds, in addition to being located in different parts of the city, which can generate a cross contagion (Begum & Sehrin, 2011).…”
Section: Discussionmentioning
confidence: 75%
“…Columbicola Ewing, 1929 Columbicola columbae (Linnaeus, 1758) ( ment) wider and more robust compared to the female that has it in the form of a brush and the vulvar segment of the female in two lobes (Eichler, 1953 Comment: Columbicola columbae is a cosmopolitan ectoparasite common in pigeons, and whose specific association has been reported in Peru (Naupay et al, 2015;Castro et al, 2017), Colombia (Pérez et al, 2015), Brazil (De Oliveira et al, 2000), Chile (González et al, 2004) to name a few, thus coinciding with our results. Mey, 2004 ( Fig.…”
Section: Ischnoceramentioning
confidence: 99%
“…Respecto a los ectoparásitos es importante considerar los estudios realizados por (18) quien realiza un enfoque de los ectoparásitos encontrados en el cuerpo de las palomas. Realiza la inspección de la superficie externa de la cabeza, cuello, pecho, dorso y alas, determinando que el 93.1% (14.9 ± 15.8 de abundancia media total) de las palomas estuvieron infestadas con uno o más ectoparásitos; asimismo, el 100% de los machos y 83.3% de las hembras estuvieron parasitados.…”
Section: Discussionunclassified
“…Matriz de distancia genética (Nei, 1972) tos. La paloma doméstica tiene usualmente alta carga parasitaria (Naupay et al, 2015). Los individuos melánicos reflejan menor susceptibilidad a endoparásitos, y tienen una mayor respuesta inmune frente a ellos, que individuos de fenotipos más claros (Jacquin et al, 2011).…”
Section: Discussionunclassified
“…Por lo tanto, esos resultados sugieren que la coloración podría reflejar estrategias alternativas para hacer frente a la urbanización a través de diferentes exposiciones o susceptibilidad a parásitos (Naupay et al, 2015). En el presente estudio era de esperarse que las mayores frecuencias alélicas las mostrarían los marcadores melanóticos como Spread y Checker, indicando que la distribución espacial de las palomas podría estar condicionadas a las presiones parasitarias, conllevando a una relación de variabilidad de fenotipos según el grado de urbanización.…”
Section: Discussionunclassified